Umbilical hernia. lts rational treatment - Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto; Cordal, Adriana (Cirugía del Uruguay, 1984)
Au't hors discuss umbilical hernia with reference to a series of 180 cases in which !he clinical, pathological, therapeutic and evolulive aspects are studied. A recurring factor in same is !he predisposition of the physical characteristics al the seat of the hernia and primarily, !he morphological aspect. The size of the parietal defect is considered an indicator of the possibility of recidivation.